Mitigating Re-Entrant Etch Profile Undercut in Au Etch with an Aqua Regia Variant. Issue 8 (1st August 2022) - Ferguson, Mark; Najah, Mohamed; Banville, Frédéric; Boucherit, Mohamed; Miriyala, Naresh; Renaud, Jacques; Fréchette, Luc; Boone, François; Ecoffey, Serge; Charlebois, Serge A.
Abstract : We investigate the re-entrant undercut profile resulting from Au wet etching for patterning micron range thick films using an aqua regia-based solution in comparison with an iodine-iodide-based commercial etchant. Our work discriminates between two undercutting mechanisms: galvanic acceleration of etch rate at the Au adhesion or barrier layer, and delamination-based undercutting. We tracked etch outcomes of feature size reduction from photoresist size, undercut Au in cross-section and lift-off of small (5–10 μ m) features. Results indicate that galvanic undercutting is well-mitigated by the aqua regia solution compared to commercial etchant results. Good Au adhesion eliminates undercut for 500 nm-thick Au and mitigates it by ∼80% for 1 μ m-thick Au. We discuss the electrochemical origin of this mitigated galvanic undercut.